Transformative Literacy Training for English Students: The Impact of Movie-Based Learning Methods - Karimaliana, Karimaliana; Ramadhan, Syahrul; Mukhaiyar, Mukhaiyar (VELES Voices of English Language Education Society, 2023)
This study investigates the impact of movie-based training on enhancing English literacy among high school students. Employing a quantitative approach, it explores the relationship between movie-based English communication training and its effect on literacy skills. The research involves 57 high school students from private schools. The SEM PLS technique was utilized for data analysis. Validity tests confirmed the reliability of all survey items, with indicators exceeding a 0.5 loading factor. The study's focus is the direct impact of understanding English communication through movies on student literacy. Notable findings were observed at Ar-Raudhatul Hasanah private school, where a significant correlation was established, indicated by a p-value of less than 0.05 and a t-value of 6.774, surpassing the threshold of 2.008 indicating a significant influence of movie-based training on enhancing English communication skills. This suggests that such training could be beneficial not only for students but for a broader audience as well.